INTERVAL SELISIH RATA-RATA DENGAN METODE BOOTSTRAP PERSENTIL - Akhmad, Fauzy (MATEMATIKA, 2003)
We usually use traditional method to construct interval for the difference between two population means. This interval needs an assumption that sample is random and has normal distribution (symmetric). This article will discuss another method, namely bootstrap percentile. Bootstrap percentile method is more potential in constructing this interval and give shorter interval than the traditional method. This method does not need an assumption that the sample has to have a normal distribution. Â